Physiotherapists’ barriers and facilitators to the implementation of a behaviour change-informed exercise intervention to promote the adoption of regular exercise practice in patients at risk of recurrence of low back pain: a qualitative study - Moniz, A (2024)
Background: Recurrences of low back pain (LBP) are frequent and associated with high levels of disability and medical costs. Regular exercise practice may be an effective strategy to prevent recurrences of LBP, however, the promotion of this behaviour by physiotherapists seems to be challenging. This study aims to explore physiotherapists' perceived barriers and facilitators to the implementation of a behaviour change-informed exercise intervention to promote the adoption of regular exercise practice by patients at risk of recurrence of low back pain. Methods: Two focus groups with primary healthcare physiotherapists were conducted, based on a semi-structured interview schedule informed by the Behaviour Change Wheel, including the Capability, Opportunity, Motivation-Behaviour (COM-B) model and the Theoretical Domains Framework (TDF). All focus groups were held through videoconference, audio and video recorded and transcribed verbatim. A deductive content analysis, using a coding matrix based on the COM-B and TDF, was performed by two independent researchers. A third researcher was approached to settle disagreements. Results: In total, 14 physiotherapists participated in the focus groups. The analysis revealed a total of 13 barriers (4 COM-B components and 7 TDF domains) and 23 facilitators (5 COM-B and 13 TDF) to physiotherapists' implementation of a behaviour change-informed exercise intervention. The most common barriers were the lack of skills and confidence to implement the proposed intervention. These were explained by the fact that it differs from the usual practice of most participants and requires the learning of new skills applied to their contexts. However, for those who had already implemented other similar interventions or whose rationale is aligned with the new intervention, there seemed to exist more positive determinants, such as potential benefits for physiotherapists and the profession, improvement of quality of care and willingness to change clinical practice. For others who did not previously succeed in implementing these types of interventions, more context-related barriers were mentioned, such as lack of time to implement the intervention, schedule incompatibilities and lack of material and human resources. Conclusions: This study identified modifiable barriers and facilitators to physiotherapists' implementation of a behaviour change-informed exercise intervention for patients at risk of recurrence of LBP in primary healthcare. The findings of this study will allow the systematic and theory-based development of a behaviour change-informed training programme, aimed at physiotherapists and supporting the successful implementation of the exercise intervention.